2015
DOI: 10.1016/j.jobe.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Energy retrofit of historic buildings: Environmental assessment of cost-optimal solutions

Abstract: a b s t r a c tThis paper describes the implementation of an integrated cost optimality and environmental assessment involving alternative energy efficiency retrofit packages for a building that dates from the beginning of the 20th century. A building typical of the building stock in the centre of Coimbra (located in the central region of Portugal and recently classified as a UNESCO World Heritage Site) was used to illustrate the methodology presented. The results were also analysed for the same building in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 27 publications
(27 reference statements)
3
43
0
Order By: Relevance
“…10. This confirms that credit lines with lower interest rates can encourage investment in energy retrofit and efficiency measures with lower environmental impact, a fact also detected in previous studies (Tadeu, Rodrigues, Tadeu, Freire, & Simões, 2015). However, GB + ST T without insulation remains the best investment option, since GB without insulation does not meet the minimum national requirements.…”
Section: Return On Investment Approachsupporting
confidence: 86%
“…10. This confirms that credit lines with lower interest rates can encourage investment in energy retrofit and efficiency measures with lower environmental impact, a fact also detected in previous studies (Tadeu, Rodrigues, Tadeu, Freire, & Simões, 2015). However, GB + ST T without insulation remains the best investment option, since GB without insulation does not meet the minimum national requirements.…”
Section: Return On Investment Approachsupporting
confidence: 86%
“…According to data from the historical series, the rate of urbanization in Brazil of 80% in 2002 reached 84.36% in 2010 [44], with an increase in concentration in the state capitals and some medium-sized cities, boosting the construction industry segment.…”
Section: Local Impacts Of Construction Sites and Their Main Regulatormentioning
confidence: 99%
“…In the construction market, there are also databases of sector organizations such as the Civil Construction and Public Works Industry Association of Portugal and those for private sectors such as CYPE Prices Generator maintained [82] which bring together data from 27 countries with languages of Latin origin. Beyond being used in the budget, CYPE Prices generator has also been adopted as an auxiliary tool to estimate the use of resources in different studies on environmental issues such as life cycle analysis and rehabilitation [35,83,84].…”
Section: Construction Activities Selectionmentioning
confidence: 99%
“…In addition, studies taking an environmental assessment perspective of cost-optimal solutions for building renovation are scarce and geographically inconsistent. Previous research includes multidimensional Pareto optimization using LCA in three residential buildings located in France, Sweden and The Netherlands [23], an optimization matrix development for a multistorey residential building in Northern Italy [24] and an integrated life-cycle assessment and cost optimality assessment at a historic building in Portugal, which showed that these kind of buildings (which do not have to comply with energy and thermal codes) can achieve significant energy savings (taking into consideration also economic and environmental costs) [25].…”
Section: Introductionmentioning
confidence: 99%